The mind of Thomas Jefferson - Onuf, Peter S. (Charlottesville : University of Virginia Press, 2007)
In The Mind of Thomas Jefferson, one of the foremost historians of Jefferson and his time, Peter S. Onuf, offers a collection of essays that seeks to historicize one of our nation's founding fathers. Challenging current attempts to appropriate Jefferson to serve all manner of contemporary political agendas, Onuf argues that historians must look at Jefferson's language and life within the context of his own place and time. In this effort to restore Jefferson to his own world, Onuf reconnects that world to ours, providing a fresh look at the distinction between private and public aspects of his character that Jefferson himself took such pains to cultivate. Breaking through Jefferson's alleged opacity as a person by collapsing the contemporary interpretive frameworks often used to diagnose his psychological and moral states, Onuf raises new questions about what was on Jefferson's mind as he looked toward an uncertain future. Particularly striking is his argument that Jefferson's character as a moralist is nowhere more evident, ironically, than in his engagement with the institution of slavery. At once reinvigorating the tension between past and present and offering a new way to view our connection to one of our nation's founders, The Mind of Thomas Jefferson helps redefine both Jefferson and his time and American nationhood.
Making sense of Jefferson -- American synecdoche : Thomas Jefferson as image, icon, character, and self (with Jan Ellen Lewis) -- A declaration of independence for diplomatic historians -- Thomas Jefferson, federalist -- The revolution of 1803 -- Thomas Jefferson and the expanding union -- The Louisiana Purchase and American federalism -- Jefferson's religion : priestcraft, enlightenment, and the republican revolution -- Liberty to learn -- Thomas Jefferson's military academy : a summary view -- Thomas Jefferson, race, and national identity -- Every generation is an "independant nation" : colonization, miscegenation, and the fate of Jefferson's children -- Jefferson, morality, and the problem of slavery (with Ari Helo).
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Jefferson, Thomas, -- 1743-1826 -- Political and social views; Jefferson, Thomas, -- 1743-1826 -- Philosophy; Jefferson, Thomas, -- 1743-1826 -- Influence; Jefferson, Thomas, -- 1743-1826 -- Influence; Jefferson, Thomas, -- 1743-1826 -- Philosophy; Jefferson, Thomas, -- 1743-1826 -- Political and social views; Jefferson, Thomas, -- 1743-1826 -- Pensée politique et sociale; Jefferson, Thomas, -- 1743-1826 -- Philosophie; Jefferson, Thomas, -- 1743-1826 -- Influence; Jefferson, Thomas, -- 1743-1826; Jefferson, Thomas -- Politik und Gesellschaft; Jefferson, Thomas -- Aufsatzsammlung; Jefferson, Thomas; HISTORY -- United States -- State & Local -- General; HISTORY -- United States -- Revolutionary Period (1775-1800); Influence (Literary, artistic, etc.); Philosophy; Political and social views